Coastal Water Quality Monitoring and Modelling Off Chennai City. (2015) - Mishra, Pravakar; Panda, Uma Sankar; Pradhan, Umakanta; Kumar, C. Saravana; Naik, Subrat; Begum, Mehmuna; Ishwarya, J.
Abstract: Knowing the coastal water quality is vital from the perspectives of coastal resource usage and management. Worldwide, along many urbanized coastal regions, massive input of industrial, agricultural and sewage effluents have tremendous impact by altering the nutrient characteristics, triggering toxic algal blooms affecting biodiversity, fisheries, tourism, recreation and other activities. Since 1990s, extensive monitoring of the coastal waters along the Indian coast have been undertaken by the Ministry of Earth Sciences (MoES). This paper evaluates the seasonal and monthly variations of water quality parameters viz., salinity, pH, dissolved oxygen, nutrients, chlorophyll- a, primary productivity, phyto- and zooplankton, pathogen bacteria off Chennai metropolitan. Low dissolved oxygen (∼ 5 mg/l) levels and high concentration of nutrients (phosphates, nitrates) recorded in the Cooum and Adyar river waters. Water quality data collected on a monthly basis at 30 locations along the coast during January'2013- December'2014 reveals a strong seasonal trend. Excess phosphorous (P) and nitrogen (N) lead to eutrophication resulting occurrence of algal blooms, high chlorophyll- a (230.24 mg m -3 ) and phaeocystis sp.a toxin producing bloom was observed during spring (February-April) months along the coast within the breaker's zone. Increase in pathogenic bacteria to an alarming level is recorded and relatively lower concentration is correlated to dilution and rainfall. Phytoplankton species diversity index ( H ) falls under the category of 'Poor' (H=<2.0). Numerical modeling is being applied for assessing the fate and transport of pollutants for development of water quality prediction system for the coast.